The influence of different connecting rod configurations on the stability of the Ilizarov Frame: A biomechanical study - Thiart, Gerhard (Department of Health and Rehabilitation Sciences, 2018)
Background: The Ilizarov external fixator (IEF) is frequently used in trauma and elective orthopaedics. Many of its biomechanical variables (ring size; wire diameter; wire number; half pins versus wires; etc.) and their influence on stability and stiffness have been investigated. There is however a paucity in the literature regarding the influence of the connecting rod numbers and configurations between the rings on IEF stability. Objectives: Primarily to compare the stability between four and three rod IEF configurations. Secondarily to assess the difference in stability between symmetrical and asymmetrical spacing of the IEF rods. Methods: A custom jig was designed to facilitate mounting of a basic two ring IEF in a hydraulic press. Controlled centre and off centre (thus simulated bending) axial loading was then applied across the frame. The configurations were loaded up to 4000 Newtons. The frame deformation was plotted and the data was then analysed and interpreted. Results: Negligible differences were observed between different four and three rod configurations as long as the applied force at the loading point (LP) was within the area of support (AOS) created by the rods. The different four rod constructs were always more stable than the three rod constructs during bending. Conclusions: There is comparable stiffness between a four rod and a three rod IEF construct as long as the loading point (LP) is within the area of support (AOS) created by the rods. A four rod IEF is stiffer than a three rod IEF in bending.